2015
DOI: 10.31018/jans.v7i2.718
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization and morphological study of Azotobacter isolates

Abstract: Among the diazotrops, great attention has been paid to the genus Azotobacter and its role in increasing the growth and health of plants. In the present study, forty two strains of Azotobacter were isolated from soil. These strains were purified and characterized through microscopical and biochemical test for cell shape, pigmentation, colony size, Gram reaction and catalase activity were identified as Azotobacter sp These strains showed wide variability to these characters. Among 42 isolates, 7 were single cocc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 8 publications
8
5
0
1
Order By: Relevance
“…The isolates were studied for their carbon source utilization. These results confirm that these isolates belong to the genus Azotobacter [15].…”
Section: Resultssupporting
confidence: 85%
“…The isolates were studied for their carbon source utilization. These results confirm that these isolates belong to the genus Azotobacter [15].…”
Section: Resultssupporting
confidence: 85%
“…The highest amount of N 2 was fixed by Azo1 while the lowest by Azo22. Upadhyay et al [13] reported the amounts of N 2 fixed by different Azotobacter strains ranged from 18.88 to 6.04 mg g -1 sucrose and is in close agreement with the results of N 2 fixation in the present study.…”
Section: Detection Of Nitrogen Fixing Activitysupporting
confidence: 93%
“…Isolation of Azotobacter sp. from rhizospheric soils was done by the procedure described by Upadhyay et al [13]. The rhizospheric soil samples collected from the districts of Rajasthan viz.…”
Section: Methodsmentioning
confidence: 99%
“…The cell morphology is pleomorphic (Upadhyay, Kumar, Singh, & Singh, 2015), usually straight Bacilli with rounded ends becoming more ellipsoidal or coccus (Figure 1). Azotobacter is a chemo-organo heterotrophic organism that forms cysts in under drought stress and produced capsules (Mukhtar, Bashir, & Nawaz, 2018) which structurally consisted of polysaccharide hence the name become exopolysaccharide (Gauri, Mandal, & Pati, 2012).…”
Section: Azotobacter Morphologymentioning
confidence: 99%